Recent oceanic changes in the Arctic in the context of long‐term observations. Issue 8 (1st December 2013) - Polyakov, Igor V.; Bhatt, Uma S.; Walsh, John E.; Abrahamsen, E. Povl; Pnyushkov, Andrey V.; Wassmann, Paul F.
Abstract : This synthesis study assesses recent changes of Arctic Ocean physical parameters using a unique collection of observations from the 2000s and places them in the context of long‐term climate trends and variability. Our analysis demonstrates that the 2000s were an exceptional decade with extraordinary upper Arctic Ocean freshening and intermediate Atlantic water warming. We note that the Arctic Ocean is characterized by large amplitude multi‐decadal variability in addition to a long‐term trend, making the link of observed changes to climate drivers problematic. However, the exceptional magnitude of recent high‐latitude changes (not only oceanic, but also ice and atmospheric) strongly suggests that these recent changes signify a potentially irreversible shift of the Arctic Ocean to a new climate state. These changes have important implications for the Arctic Ocean's marine ecosystem, especially those components that are dependent on sea ice or that have temperature‐dependent sensitivities or thresholds. Addressing these and other questions requires a carefully orchestrated combination of sustained multidisciplinary observations and advanced modeling.